The institutional theory trend of land organization and land planning development - Tretiak, A.; Tretiak, V.; Priadka, T.; Kapinos, N. (Land Management, Cadastre and Land Monitoring, 2021)
Abstract. Land planning specialization of land relations and land use system has significantly strengthened the role and place of land planning activities in the development of the country's economy and its territories. However, the theory of land organization and land planning does not keep up with the demands of practice. The functions, subject and objects of land organization and land planning are declared to a limited extent. Therefore, the purpose of the study is to substantiate the current development of land organization and land planning in Ukraine on the basis of the latest institutional and behavioral economic theory. It is substantiated that land planning activity is a socio-economic institution that provides trust, understanding and   in the socio-economic area, through professional processing, submission and interpretation for users of land information about the facts and processes of organizations (institutions). In the narrow sense the land planning is the Institution of transformation using specific methods, rules (its formal component) and professional skills and judgments (informal component of the institution) of land managing facts in the language of numbers for understanding and manageability of all subjects of the socio-economic area. In a broad sense, land planning as an institution forms a certain face of land-tenure and land-use, state land institutions, public and other organizations (institutes) who organize and manage the use and protection of land and other natural resources and provide important informational content of local, regional, national and global socio-economic areas. The institution of land planning is primarily characterized by the state of the informal component, its ability to influence the adoption and compliance with the «rules of the game» through «organizations-institutions» (primarily associations of professional land surveyors). Influence the effective representation of management and economic activities related to land in society. This increase in theoretical ideas opens up new ways to develop land  planning and, consequently, land reform measures. Its scientific and legal components («rules of the game») are increasingly based on ideas, the influence of the professional environment, which should become more and more organizationally united. On the other hand, the institutional theory of land  planning opens the possibility and substantiates the need for the use of state regulatory bodies, scientific schools, professional associations of land surveyors, the ideology of «land planning engineering» and «land planning imperialism» in land policy.Keywords. Institutional theory, land organization, land planning, land planning science, land planning activities.